Tuturan Melarang dalam Film Spirited Away - Oktaviani Saputri (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2019)
The Purpose of this study is to describe the use of directive speech acts of prohibition in the Spirited Away movie which are based on the pattern of prohibitions in Japanese. It also aims to find out the factors that influence the prohibition of speech based on the context of the conversation and categorized them into direct or indirect speech. The data of this research were taken from the utterance of the characters containing the directive speech acts of prohibition. The use of prohibition directive speech acts is analyzed based on the prohibition pattern in Japanese in accordance with the theory of Namatame. This type of research uses the qualitative descriptive research method with a pragmatic approach. From the results of data analysis it was found that the use of illocutionary speech forms directly prohibits,which are: the patterns of Â ~ V ru na, ~ te wa ikenai, ~ naide, ~ dame, and ~ janai. Ilocutionary forms are directly used by people who have strong authority over their partners. With his authority the speaker does not need to use indirect speech which usually emphasizes modesty.